2020
DOI: 10.3390/ma13030720
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatments and Critical Quenching Rates in Additively Manufactured Al–Si–Mg Alloys

Abstract: Laser powder-bed fusion (LPBF) has significantly gained in importance and has become one of the major fabrication techniques within metal additive manufacturing. The fast cooling rates achieved in LPBF due to a relatively small melt pool on a much larger component or substrate, acting as heat sink, result in fine-grained microstructures and high oversaturation of alloying elements in the α-aluminum. Al–Si–Mg alloys thus can be effectively precipitation hardened. Moreover, the solidified material undergoes an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This is a result which originates from the same principle, mainly the rapid cooling of the melt to a solid, which forms the fine cellular structure, followed by the rapid quenching of the solidified material from solidification temperature to the process preheating temperature. These quenching rates cannot be reproduced by means of heat treatments and, therefore, lead to a maximum of dissolved alloying elements in the oversaturated α-Al crystals [38]. This, in turn, benefits the solid solution hardening, but more importantly, the possible precipitation hardening of these alloys, whereby the artificial aging of the just solidified and quenched material starts instantaneously during the process, due to the common process temperatures of around 200 °C being in the regime of artificial aging temperatures of Al-Si-Mg alloys.…”
Section: Tensile Strength and Compressive Behaviourmentioning
confidence: 99%
“…This is a result which originates from the same principle, mainly the rapid cooling of the melt to a solid, which forms the fine cellular structure, followed by the rapid quenching of the solidified material from solidification temperature to the process preheating temperature. These quenching rates cannot be reproduced by means of heat treatments and, therefore, lead to a maximum of dissolved alloying elements in the oversaturated α-Al crystals [38]. This, in turn, benefits the solid solution hardening, but more importantly, the possible precipitation hardening of these alloys, whereby the artificial aging of the just solidified and quenched material starts instantaneously during the process, due to the common process temperatures of around 200 °C being in the regime of artificial aging temperatures of Al-Si-Mg alloys.…”
Section: Tensile Strength and Compressive Behaviourmentioning
confidence: 99%
“…A recently published study by our research group [22] showed that the critical cooling rate necessary to achieve appreciable age-hardening for Laser-powder bed fused Al-Si-Mg ranged between 11 to 15 K/s under vacuum condition, whereas a quenching rate of 5 K/s was sufficient for cast reference material.…”
Section: Introductionmentioning
confidence: 98%
“…[22,23]. In recent years, annealing heat treatment has attracted wide attention due to its advantages of easy operation, mature technology and low cost [24][25][26]. For the most pure Al alloys, the recovery process starts at 95 • C~150 • C, while the recrystallization process starts at 200 • C~300 • C [27].…”
Section: Introductionmentioning
confidence: 99%